Dermatoscopic, Histological and Confocal Microscopic Analysis of a Kissing Nevus of the Penis - Alexander Bianchi; Alfonso Baldi; Andrea Farabini; Lorenzo Nibid; Vincenzo Roberti; Giovanni Pellacani; Dmitry V. Kazakov; Michele Donati (MDPI AG, 2023)
Kissing nevus is a congenital melanocytic neoplasm arising in those parts of the body that split at some point during embryological development (i.e., eyelid; penis), resulting in two adjacent melanocytic nevi. To date, 23 cases of kissing nevus of the penis have been described, and dermatoscopic and histological findings are available in 4/23 cases. We report a dermatoscopic, histological and confocal microscopic analysis in a new case of the kissing nevus of the penis in a 57 years old man. Dermatoscopic analysis showed large globules in the central area and a peripheral pigment network; the histological examination confirmed the presence of an intradermal melanocytic nevus with minimal junctional component and congenital features. Moreover, we reported, for the first time, confocal microscopy findings in the kissing nevus of the penis, revealing the presence of dendritic cells in correspondence with the epidermis and suggesting a state of cellular activity. Considering the clinicopathological features of the lesion, a conservative approach was adopted, and a clinical follow-up was planned after six months.